The Family violence and physical abuse, two aspects of the same problem (Legal journal - Research in Legal and Social Sciences, 2017)
Much has been written about the elementary innovations of the current Penal Code and its different modifications introduced in the transition of its application with the purpose of a better adaptation or a more convenient foreign legal adoption in the national positive law. With the purpose of establishing, from the State, a protection to the family or to the physical integrity in specific, rules have been typified or created that better qualify a certain behavior, as a criminal type of current application: Family Violence. This is the criminal type finally adopted by national legislation and is the consequence of a long struggle by women and organizations committed to the matter, in defense of the rights of women and more specifically of those who, in the family sphere, they are the object of aggression of a physical, psychological or sexual nature, which in the long run translates into family disorders. It is known that the State establishes and promotes public policies whose purpose is to avoid the violation of a fairly victimized fringe around the matter. The Penal Code itself, in articles 14, 49, 54, 60, consistent with other chapters and articles, imposes the obligation to take reason. In the Penal Code (Law 1160/97) Family Violence has been classified as a punishable act, by accurately defining it as a criminal figure adopted by State criminal policy, to obtain encouraging results that allow establishing a decrease in cases of violence intrafamily.
Keywords: aspects of violence; victims; physical abuse; family violence